Metashinobius gen. nov., the second Asian genus with uncleared subfamily placement of Trechaleidae (Araneae, Lycosoidea) from southwest China, with the description of a new species - Yufan Cheng; Jie Liu; Mian Wei (Biodiversity Data Journal)
Trechaleidae Simon, 1890 is a relatively small spider family comprising 17 genera and 136 species, most of which are distributed in South America and only one genus and three species are distributed in Asia; however, these have never been reported in southwest China.A new genus, Metashinobius gen. nov., is established, based on a new species from Guizhou Province, southwest China: Metashinobius hikariae sp. nov. (♂). This is the second Asian genus of Trechaleidae. Diagnosis, detailed descriptions, colour illustrations and distribution map of the new species are provided. The type specimen of the new species is deposited in the Centre for Behavioural Ecology and Evolution (CBEE), Hubei University, Wuhan, China.